1988
DOI: 10.1063/1.342476
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced fluorescence spectroscopy for the determination of the absolute density and spatial distribution of Si atoms in a SiH4-He-Ar glow discharge

Abstract: We report on the absolute density and the spatial distribution of silicon atoms in a SiH4-He-Ar dc glow discharge measured by the laser-induced fluorescence method. The absolute sensitivity of the fluorescence-photon-counting system was calibrated by using the same system to measure Rayleigh scattering by Ar gas in the discharge chamber. The fluorescence quantum efficiency and the polarization degree of emitted light were measured to confirm the absence of excited-state quenching induced by collisions with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Airway-parenchymal relationships critically influence the development of obstructive airway disease [7,9]. Litonjua et al [37] and Parker et al [38] determined that the FEF25-75/FVC ratio, a measure of dysanapsis, was negatively associated with the degree of methacholine airway responsiveness, implying small airway size increases the risk of airway obstructive disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Airway-parenchymal relationships critically influence the development of obstructive airway disease [7,9]. Litonjua et al [37] and Parker et al [38] determined that the FEF25-75/FVC ratio, a measure of dysanapsis, was negatively associated with the degree of methacholine airway responsiveness, implying small airway size increases the risk of airway obstructive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Airway hyperresponsiveness is related to the development of asthma and may be genetically determined [39,40]. Additionally, the prevalence of asthma and wheezing negatively correlates with airway size as evidenced by increased prevalence in prepubertal males [41] who have smaller airways [9,42] compared with females. Silverman et al reported that genetic determinants of lung function likely represent determinants of COPD and asthma [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand radical production in SiH 4 /H 2 plasmas, SiH and SiH 2 radicals have been studied under both a-Si:H and mc-Si growth conditions by optical emission spectroscopy (OES) and laser-induced fluorescence (LIF) spectroscopy. [1][2][3][4] Under a-Si:H film growth conditions, the contribution of SiH 3 radicals to a-Si:H film growth and the dynamic behavior of SiH 3 radicals have been studied by means of infrared resonant laser absorption spectroscopy (IRLAS) in a RF plasma with parallel electrodes 5) and by cavity ringdown (CRD) spectroscopy in expanding thermal plasmas. 6,7) These measurements showed that a SiH 3 radical is by far the dominant contributor to a-Si:H growth, due to its higher density and longer lifetime in the plasma than SiH X (X < 3) radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mass spectrometry, [1][2][3] laser-induced fluorescence ͑LIF͒ based techniques, [4][5][6][7][8][9][10][11][12][13] ultraviolet absorption spectroscopy, [14][15][16] and intracavity 17,18 and infrared laser 19,20 absorption techniques, recently also cavity ring down absorption spectroscopy ͑CRDS͒ has been introduced in the field of SiH 4 plasmas. This sensitive, and relatively easy-to-apply diagnostic technique 21 has already been used for the detection of SiH 3 , [22][23][24] SiH 2 , 18 and nanometric Si-based particles.…”
Section: Introductionmentioning
confidence: 99%